1987
DOI: 10.1002/j.1460-2075.1987.tb02681.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction and use of chimeric SPR/phi 3T DNA methyltransferases in the definition of sequence recognizing enzyme regions.

Abstract: Multispecific DNA methyltransferases (Mtases) of temperate Bacillus subtilis phages SPR and phi 3T methylate the internal cytosine of the sequence GGCC. They differ in their capacity to methylate additional sequences. These are CCGG and CC(A/T)GG in SPR and GCNGC in phi 3T. Introducing unique restriction sites at equivalent locations within the two genes facilitated the construction of chimeric genes. These expressed Mtase activity at a level comparable to that of the parental genes. The methylation specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…Unfortunately, there is only a limited number of direct experimental approaches backing this hypothesis, mostly dealing with the construction of new chimeric proteins by fusing cloned genes (3)(4)(5). These genetic manipulations have opened new insights into studies of the relationships between molecular structure and the biological function of proteins-e.g., it has been demonstrated that reconstruction of an enzyme by domain substitution between two proteins that share extensive amino acid sequence similarity resulted in the switch of substrate or catalytic specificity (6)(7)(8).…”
mentioning
confidence: 99%
“…Unfortunately, there is only a limited number of direct experimental approaches backing this hypothesis, mostly dealing with the construction of new chimeric proteins by fusing cloned genes (3)(4)(5). These genetic manipulations have opened new insights into studies of the relationships between molecular structure and the biological function of proteins-e.g., it has been demonstrated that reconstruction of an enzyme by domain substitution between two proteins that share extensive amino acid sequence similarity resulted in the switch of substrate or catalytic specificity (6)(7)(8).…”
mentioning
confidence: 99%
“…The a and ,B ORFs overlap in the middle of the normally poorly conserved region in which, in other modification methylases, the specific recognition site of the protein is thought to be encoded (1). This could mean either that the whole function occurs on just one of the proteins or that the a-and 3-encoded proteins perfectly fit together when active.…”
mentioning
confidence: 99%
“…A wealth of sequence information (21,27), mutational analysis (41), domain swap experiments (1,20), biochemical studies (4,42), and crystal structures for two enzymes (M.HhaI and M.HaeIII) (19,29) support the view that prokaryotic DNA (cytosine-5) MTases (C5-MTases) share a common architecture and catalytic mechanism. C5-MTases contain 10 conserved amino acid sequence motifs and a variable region between conserved motifs VIII and IX.…”
mentioning
confidence: 94%